IN SEARCH OF ROADMAP FOR NIGERIA’S NATIONAL DEVELOPMENT: RESTRUCTURING OR ATTITUDINAL CHANGE? - ODUM, Mbanefo (Socialscientia: Journal of Social Sciences and Humanities, 2019)
Past efforts geared towards engendering national development in Nigeria have yielded unsatisfactory results and this has led to the continuing search for an appropriate model or prescription that would deliver the country from her problems. In recent times, the issue of restructuring has occupied the centre stage of the national discourse and seemingly presented in some quarters as a panacea for overcoming the national developmental challenges. While not denying that the country has several structural defects, it is necessary to appraise Nigeria’s situation with a view to determining whether her problem lies with the structuring of the country per se, or whether it is borne out of attitudinal issues. To achieve this objective, this study shall adopt the documentary method of data collection to be interpreted through content analysis. The framework for analysis revolves around the Structural Change theory. The paper argues that while there is need to embark on some levels of restructuring of the Nigerian State, there is greater need to engender attitudinal change within the system so as to avoid the reoccurrence of the existing problems even after the state must have been restructured.